Cognitive stimulation program in mild cognitive impairment A randomized controlled trial - Gomez-Soria,Isabel (2020)
Abstract. Non-pharmacological cognitive interventions in mild cognitive impairment have demonstrated promising results in preventing or delaying cognitive impairment and functional disability. Cognitive stimulation seems to improve and maintain cognitive and social activity. Objective: This study aimed to evaluate the impact of a cognitive stimulation program in mild cognitive impairment (MCI) at the cognitive level on activities of daily living (ADLs), and levels of anxiety and depression. Methods: A randomized controlled single-blind trial involving 122 non-institutionalized elderly with a MEC-35 score of 24-27 was conducted. The intervention group (n=54) received the intervention (10-week cognitive stimulation program) and was compared with a control group (n=68) that received no intervention. Follow-up assessments were conducted post-test and at 6 months post-test. The primary outcome was cognitive function determined by changes in scores on the Spanish version (MEC-35) of the Mini-Mental State Examination, while the secondary outcomes were measured by the Barthel Index, Lawton and Brody Scale, Goldberg Questionnaire (anxiety sub-scale) and the Yesavage Geriatric Depression Scale (15-item version). Results: The intervention group showed a significant improvement in cognitive function at both timepoints, post-test and 6-month follow-up. The Barthel Index was higher in the intervention group, but only on the post-test analysis. The intervention did not improve the performance of instrumental ADLs or depression or anxiety levels. Conclusion: The findings showed cognitive improvements in an elderly population with MCI in the short and medium-term and improved basic ADLs in the short term. Clinicaltrials.gov Identifier: NCT03831061.